Peranan cairan tape ketan pada pembentukan sweet curdled milk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Tape ketan juice which contains metabolites of tape fermentation will he used in the formation of mill curd. The proteolytic activity, microbiological and chemical analysis of tape ketan juice and formation of tht curd itself were carried out. The proteolytic activity of tape ketan juice resulted from fermentation on the fourth day was found to be 615.9 unit with 1.33 mM of Km and 2.63 mM of Total microbes of tape ketan juice was about 1.5 x 106 chi/nil, which were dominated by two different yeasts. The two of dominant yeast have proteolytic activity and capable of coagulating milk. The pH of tape ketan juice was 4, 0.3% of acidity, 4% of ethanol and 39.9% of glucose. The formation of curd was achieved by addition of 5-75% tape ketan juice of filtered sterilized tape ketan juice with 0.45 Am membrane filter, 50-75% pH 4 of heat sterilized tape ketan juice, 25-75% pH 4 of acetic buffer, but was not produced by 5-75% of 4% ethanol. Coagulation of milk may occur due to both activities of proteolytic and the acidity.